2x+6=69+-5x

Simple and best practice solution for 2x+6=69+-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+6=69+-5x equation:


Simplifying
2x + 6 = 69 + -5x

Reorder the terms:
6 + 2x = 69 + -5x

Solving
6 + 2x = 69 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
6 + 2x + 5x = 69 + -5x + 5x

Combine like terms: 2x + 5x = 7x
6 + 7x = 69 + -5x + 5x

Combine like terms: -5x + 5x = 0
6 + 7x = 69 + 0
6 + 7x = 69

Add '-6' to each side of the equation.
6 + -6 + 7x = 69 + -6

Combine like terms: 6 + -6 = 0
0 + 7x = 69 + -6
7x = 69 + -6

Combine like terms: 69 + -6 = 63
7x = 63

Divide each side by '7'.
x = 9

Simplifying
x = 9

See similar equations:

| 0.5(3x-5)=8 | | 6(x-1)=3(x-2) | | 2/-4/3=x | | 2/-4/3 | | 5+7(x+1)=12+10x | | x+3/4=17/18 | | 2(x+2)=1x-5 | | -10-9y=-13 | | 4/6x-2/6 | | 8/9*4/5 | | 7x-12x=-45+15 | | 4(y-3)-2y=5(3y+1) | | x-1=2(3x+7) | | 21-9x=4x+8 | | 3/6x-9/18 | | 64/1*7/8 | | 6x-5=4x-9 | | 3/4x-1+1/2x=7/16x+1/8 | | 1/2(x-6)=9 | | 5(y-4)=2(y+5)Y | | f(x)=x^3-x^2-11x+3 | | 5/6*2/3*2/7 | | x=(2.4e)/(0.68^1/5) | | 3/5*4/7*1/3 | | -9x^2+16x-14=0 | | 5(2x+3)=7(x+1) | | 0.11+0.09+720=1520 | | 17x+27x=180 | | 9/10*5/7*1/3 | | -16+2x=4x-4(4+3) | | 4x^2-15x+14=-6x+9 | | x=2.4e/(0.68)^1/5 |

Equations solver categories